2023
DOI: 10.1186/s12903-023-03257-8
|View full text |Cite
|
Sign up to set email alerts
|

White spot lesions, plaque accumulation and salivary caries-associated bacteria in clear aligners compared to fixed orthodontic treatment. A systematic review and meta- analysis

Shailaja Raghavan,
Elham S. Abu Alhaija,
Mandeep Singh Duggal
et al.

Abstract: Objective To analyse the available evidence regarding the incidence and severity of white spot lesions (WSLs), plaque accumulation and salivary caries-associated bacteria(SCB) in clear aligners (CA) verses conventional fixed (CF) orthodontic appliances. Methods Electronic searches of MEDLINE, Scopus, Embase, Google Scholar, Clinical trial registry, OpenGrey and ProQuest were done for all relevant studies. Eligibility criteria were; Randomized Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Coatings such as those containing lactoferrin or silver, gold, or copper nanoparticles may not discriminate between different types of bacteria, highlighting the importance of exploring bacteriostatic systems that prevent bacterial adsorption on the surface [ 31 ]. Therefore, further work should be conducted on bacteriostatic systems that do not allow adsorption of bacteria on the surface, such as polyethylene glycol coatings, which is an effective bacteriostatic agent [ 32 , 33 ]. The materials from which aligners are made are changing, and new materials are being used.…”
Section: Discussionmentioning
confidence: 99%
“…Coatings such as those containing lactoferrin or silver, gold, or copper nanoparticles may not discriminate between different types of bacteria, highlighting the importance of exploring bacteriostatic systems that prevent bacterial adsorption on the surface [ 31 ]. Therefore, further work should be conducted on bacteriostatic systems that do not allow adsorption of bacteria on the surface, such as polyethylene glycol coatings, which is an effective bacteriostatic agent [ 32 , 33 ]. The materials from which aligners are made are changing, and new materials are being used.…”
Section: Discussionmentioning
confidence: 99%
“…With an increasing number of patients choosing nonbracketed invisible orthodontic treatment, patients and doctors should pay more attention to the prevention and treatment of complications and the potential risks after treatment [ 7 ]. During clinical treatment, we found that in the invisible orthodontic group, many adolescent patients had white spot lesions after wearing the invisible orthodontic appliance, and the prevalence of this phenomenon in this group may not be lower than that in fixed orthodontic patients [ 8 ]. The etiology may be related to the ability of the invisible orthodontic appliance to disrupt homeostasis of the oral environment in adolescent patients and induce a series of inflammatory responses caused by changes in the microflora; the inflammatory factors involved in this process are the focus of this study [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, we classified this patient in the "high-risk" group for the onset of WSL [26], so we decided to treat her with a set of aligners. Moderate-quality evidence reveals less plaque accumulation and less salivary caries-associated bacteria in clear aligners, which might be related to the reduced incidence and severity of WSLs associated with CA when compared with fixed-multibracket appliances [27].…”
Section: Clinical Casementioning
confidence: 99%